Evaluation by Free Vibration Method of Moisture Absorption Effects in Polyamide/Carbon Fiber Laminates - Botelho, Edson Cocchieri [UNESP]; Rezende, M. C. (Sage Publications Ltd, 2010)
The use of thermoplastic composite materials in aerospace and naval fields has increased due principally to their high performance associated with low specific weight. In order to screen material behavior, the effects of external environments on the mechanical properties during usage must be clearly understood. Environmental factors such as ultraviolet radiation (UV), corrosive fluids, moisture and temperature can limit the applications of composites by deteriorating the mechanical properties over a period of time. In order to characterize composite materials, are commonly used tensile tests. Another test that can be used in order to evaluate the viscoelastic properties of thermoplastic composite materials is free vibration damping. In this work, the viscoelastic properties of polyamide 6.6/carbon fiber laminates were obtained by two types of tests: tensile and free vibration damping tests. Two families of textile polyamide/carbon fiber composites ([perpendicular to 45] and [0/90]) were obtained by hot compression molding. The present studies have been performed to explore relations between the dynamic mechanical properties and the influence of high moisture concentration of this thermoplastic laminate. The results show that the E' decrease with the increase in the exposed time for polyamide/carbon fiber composite specimens and that free vibration damping technique can be used instead of tensile test in order to know the elastic modulus.
Keywords: polyamide/carbon fiber composites; damping behavior; elastic properties; hygrothermal conditioning